PENGARUH PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI FASE F DI SMA NEGERI 1 BONJOL - Dwita, Ratni (Jurnal Edukasi dan Penelitian Matematika, 2024)
Mathematical problem-solving skills are essential for all students so that they can learn to adapt their approach to more complex problems. However, students still have a modest level of this talent. Applying an open-ended approach in learning is one of the solutions. This study sought to compare the effectiveness of conventional open-ended approach in improving such ability in class XI FASE F SMA Negeri 1 Bonjol. Using Non-Equivalent Posttest-Only Control Group Design as its research framework, this study utilizes a semi-experimental approach. Better skill improvement compared to conventional learning is the result of the open-ended method, according to data analysis.Keywords – Open-Ended, Conventional Learning, Mathematical Problem Solving Ability